Pertumbuhan dan Hasil Tiga Varietas Kedelai dengan Berbagai Interval Pemberian Air Irigasi di Lahan Sawah Beriklim Kering - Herawati, Nani; Ghulamahdi, Munif; Sulistyono, dan Eko (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Soybean (Glycine max L. Merrill) is an essential commodity due to its protein content and it is also as  functional  food which contains isoflavon as an antioxidants. Import policy is handled when there is a high demand of soybean in local market but lack of local production. This research aimed to study growth and yield of three  soybean varieties with differens watering intervals in paddy field under dry climate. This research was conducted in Sesela Village, Gunung Sari Sub District, District of West Lombok, Nusa Tenggara Barat Province from July to October 2015. This research used split plot design with three replications. The main plot was irrigation intervals every (2, 9, 16, 23, 30 days) and the sub plot was soybean varieties (Anjasmoro, Burangrang, and Tanggamus). The results showed that interaction between irrigation interval and varieties influenced plant growth and yield, such as plant height, number of leaves, leaf area, 100 seeds weight  and number of productive pod. Tanggamus variety has the highest number of pods of 146.33 and yield (4.2 ton ha-1) in paddy field. Keywords: number of leaves, productive pod, variety, yield